Multidisciplinary approach in the treatment of the sequela of anterior dentoalveolar trauma: Case report (Research, Society and Development, 2025)
Dental trauma in childhood results in physical damage to the tooth and the child, causing functional, aesthetic and psychological problems. According to the literature, trauma to deciduous teeth is common and usually occurs for the first time in children who are beginning to walk. Therefore, it is possible that new traumatic injuries may occur during the child's growth and development, which may affect the deciduous tooth and the germ of the permanent tooth in formation, as there is a close anatomical relationship between the apices of the roots of the deciduous teeth and the germ of the permanent tooth. The aim of this study is to present a multidisciplinary approach to rehabilitate children with sequelae of anterior dentoalveolar trauma. Female patient, nine years old, with early loss of tooth 61 due to trauma in early childhood, leading to root dilaceration and alteration in the eruption trajectory of tooth 21. Rapid maxillary expansion (RME) was planned, followed by prosthetic rehabilitation with a Nance prosthesis for functional and aesthetic rehabilitation. The Nance prosthesis was recommended for satisfactory rehabilitation, even if only temporarily, until the patient's growth is complete, so that a dental implant can be placed as an alternative to definitive treatment. In this study, the case reported required a multidisciplinary approach for the treatment of the sequelae of anterior dentoalveolar trauma, with orthopedic intervention using a Haas-type expansion device and a Nance prosthesis. The patient is being monitored and will be rehabilitated through a dental implant after surgical removal of the tooth.